Process Optimization of Potassium Release from K–Feldspar by Combining Calcination and Hydrothermal Method. Issue 2 (10th January 2020) - Liu, Shanke; Han, Cheng; Liu, Jianming
Abstract: An optimized process of the hydrothermal treatment of potassium feldspar (K‐feldspar) and lime to obtain a potash alternative is reported. The optimization did not change a two‐key‐step process and only modified the first step, in which K‐feldspar was calcined together with calcium carbonate. However, this modified treatment greatly improved the dissolution of K‐feldspar, and the released K+Al+Si content was increased by 43 %. Phase analysis showed that new phases (i. e., leucite, larnite, and portlandite) appeared, and the structure of K‐feldspar was destroyed during calcination. After the hydrothermal reaction (i. e., the second step), many new mineral phases were generated: bütschliite, calcite, hibschite, tobermorite, and alpha‐dicalcium silicate hydrate. Therefore, the optimized product showed better physicochemical properties. In addition, the activity of lime was investigated to evaluate its effect on the hydrothermal dissolution of K‐feldspar. The optimized hydrothermal product, as a potential commodity, was evaluated from technological and environmental points of view. Abstract : Process optimization: The optimization of the hydrothermal process between K‐feldspar and lime increased by 43 % dissolved element content, and the process was further evaluated from the views of technology and environment.